Strategies for Managing Non-Halal Funds in Sharia-Compliant Hotels Within the Context of CSR: A Perspective from Islamic Economic Law - Laras Annisa Ulfitri Nedi; Nita Astuti; Santi Susanti (Harmoni Economics: International Journal of Economics and Accounting, 2024)
One critical component in the rapidly expanding halal tourism industry is the existence of hotels catering to the needs of Muslim travelers, known as Sharia-compliant hotels. Operating within the framework of Islamic law, these hotels bear the responsibility of managing funds in accordance with Sharia principles. The management of non-halal funds within such establishments presents a complex challenge that necessitates careful consideration to ensure compliance with Islamic values while addressing financial and social aspects. This study aims to provide insights into strategies for managing non-halal funds in Sharia-compliant hotels within the framework of Corporate Social Responsibility (CSR) and from the perspective of Islamic economic law. Using a qualitative research approach with descriptive analysis through a literature review, the findings indicate that the legal status of non-halal funds may be permissible if allocated for general public welfare. Recommended management strategies include adherence to the PSAK 101 accounting standard and the application of Tafriq Shafqah principles through CSR initiatives. Non-halal funds are optimally distributed for social welfare (maslahah wa tashrif al-‘ammah) such as empowering local communities through education and training, supporting zakat and charity programs, promoting sustainable environmental management, ensuring fair employment opportunities, fostering local economic development, and enhancing public education and awareness. These efforts not only enhance the positive reputation of Sharia-compliant hotels but also contribute significantly to the economic, environmental, and social well-being of the broader community.